SOME DIFFERENCES BETWEEN THE PSYCHOLOGY OF PHYSICAL EDUCATION AND THE PSYCHOLOGY OF SPORTS - S. Kasianov; A. Zemlyanoy; E. Smolyakov (Вестник Северо-Кавказского федерального университета, 2022)
The article defines the scientific and theoretical foundations of the psychology ofphysical education and the psychology of sports. Despite the apparent and obvious similarity of these scientific directions, they have internal differences in the target settings and tasks to be solved. The authors attempt to integrate into the educational process of physical education with cadets and students of educational organizations the achievements of sports psychology in the field ofpersonality formation and the educational team. Within the framework of this approach, the teacher ofphysical training or physical education is considered as a sports psychologist who determines the personal characteristics of each student, his strengths and weaknesses, motivational and value orientations and moral and volitional abilities for continuous improvement. The paper provides recommendations on the organization of training based on modern requirements for the educational process of physical education in educational institutions of higher professional education.